Ефективність самостійної роботи студентів - Ялпачик, Володимир Федорович; Ялпачик, Владимир Федорович; Yalpachyk, Volodymyr; Буденко, Сергій Федорович; Буденко, Сергей Федорович; Budenko, Serhii (My University, 2014)
UK: У роботі наведені аспекти підвищення ефективності самостійної роботи студентів. EN: The paper describes the aspects of increasing the efficiency of independent work of students.
The effectiveness of independent work of students
Keywords: самостійна робота; мотивація; вимоги; ефективність; самостійна діяльність; параметри; independent work; motivation; requirements; efficiency